AWARENESS LEVEL OF NURSING STUDENTS REGARDING VIOLENCE AGAINST WOMEN – EXAMPLE FROM TURKEY - Gülseren ÇITAK TUNÇ; Nevin ÇITAK BİLGİN and F. Elif KILINÇ (International Journal of Eurasia Social Sciences, 2018)
_To determine the awareness levels of the young people regarding the practices concerning the elimination of violence against women in Turkey.Method_ In this research, descriptive survey method was used. Results_ 68% of the nursing students stated that they have witnessed violence while 15.5% stated that they have been exposed to violence. Most common type of violence resorted to is physical violence. The ratio of male students who declared to have been exposed to violence is higher than that of female students (p_0.001). The percentage of students who are aware of the practices and projects to combat violence against women in Turkey is 66.9%. In terms of the awareness about the practices and projects, ratios of female students are higher than male students and the difference in between is statistically significant (p_0.05). Most widely known practices and projects are “ALO 183 line”, “Family Counseling Centers” and “Child not Brides Projects”. There was not any difference between the first and fourth-year students in terms of the awareness about the practices and projects (p_0.05). Students consider the civil society organizations as the most effective structure in raising awareness about the prevention of violence against women_